TANTANGAN PEMANFAATAN HAK KEKAYAAN INTELEKTUAL SEBAGAI SOLUSI PERMODALAN [The Challenges of Utilizing Intellectual Property Rights as a Capital Solution] - Mieke Yustia Ayu Ratna Sari; Riza Yudha Patria (Law Review, 2020)
The purpose of this paper is to explore the use of IPR, especially with regard to the challenges faced in obtaining business capital. Normative legal research is used to analyze the legal issues raised in this paper. IPR, business, innovation and capital are components that work together to increase the value of a business. For business people, especially in the creative industry, IPR is an important factor in business activities. The monetization of IPR is something that must be done by business people in order to exist in any situation, because this step has an important contribution to business development. Funding guarantees and business valuations can be achieved by monetizing IPR. The implementation of IPR monetization, especially in the field of guarantee, has been supported by regulations, which are regulated in Law no. 28 of 2014 concerning Copyright and Law no. 13 of 2016 concerning Patents, but there are still challenges including technical regulations from Bank Indonesia and the absence of an appraisal institution. Both are the main keys in implementing fiduciary security using IPR objects. Therefore, strategic steps from the government are awaited by business actors, especially in the creative sector, to immediately realize appraisal institutions and prepare technical regulations related to guarantees and execution of collateral, so that the creative industry sector players can maximize their IPR assets.Bahasa Indonesia Abstrak: Tujuan dari penulisan ini adalah menggali pemanfaatan HKI khususnya berkenaan dengan tantangan yang dihadapi dalam rangka mendapatkan modal usaha. Penelitian hukum normatif digunakan untuk menganalisis isu hukum yang diangkat dalam penulisan ini. HKI, bisnis, inovasi dan modal merupakan komponen yang saling bersinergi untuk dapat meningkatkan value dari suatu usaha. Bagi pelaku bisnis, khususnya bidang industri kreatif, HKI menjadi faktor penting dalam aktivitas usaha. Monetisasi HKI menjadi suatu yang harus dilakukan oleh para pebisnis agar tetap eksis di situasi apa pun, karena langkah tersebut memiliki kontribusi penting dalam pengembangan usaha. Jaminan pendanaan dan valuasi bisnis bisa ditempuh dengan memonetisasikan HKI. Pelaksanaan monetisasi HKI khususnya di bidang penjaminan sudah didukung oleh regulasi, yakni diatur dalam UU No. 28 Tahun 2014 tentang Hak Cipta dan UU No. 13 Tahun 2016 tentang Paten, namun masih terdapat tantangan, di antaranya peraturan teknis dari Bank Indonesia dan belum adanya lembaga appraisal. Keduanya menjadi kunci utama dalam pelaksanaan jaminan fidusia menggunakan objek HKI. Oleh karena itu, diperlukan langkah strategis dari Pemerintah sangat ditunggu oleh pelaku binis, khususnya bidang kreatif, untuk segera mewujudkan lembaga appraisal dan menyiapkan regulasi teknis terkait penjaminan dan eksekusi benda jaminan, agar pelaku sektor industri kreatif dapat memaksimalkan aset HKI yang dimilikinya.